Functional near-infrared spectroscopy characteristics in children with autism spectrum disorder under animated video modeling therapy - Zhu, Chuanhua; Li, Hongwei; Zhang, Lina; Liu, Yonglu; Zhang, Yangyang; Huang, Binbin; Li, Wei (Frontiers in Neurology, 2025)
ObjectiveTo investigate the impact of animated video modeling (AVM) on the brain function of children with autism spectrum disorder (ASD) using functional near-infrared spectroscopy (fNIRS).MethodsFifteen children with ASD and 15 matched typically developing (TD) controls were enrolled. fNIRS was used to obtain 8-min data in quiet and visually stimulated states, with the dorsolateral prefrontal cortex, medial prefrontal cortex (mPFC), and bilateral occipital lobe as regions of interest (ROIs). Based on the concentration of oxygenated hemoglobin (HbO2) over time, correlation coefficient analysis was performed to calculate functional connection strength, and the intergroup disparity was compared.ResultThe ASD group showed significantly lower functional connection strength. Comparison of the ROI–ROI functional connectivity strength revealed significant differences in connectivity patterns of the right dorsolateral prefrontal lobe (RDLPFC), left dorsolateral prefrontal lobe (LDLPFC), mPFC, right occipital lobe (ROL), and left occipital lobe (LOL) with other brain regions. Extremely significant differences were found between the RDLPFC/RPMC, ROL/RPMC, LOL/RPMC, and LOL/LIPL. The functional connectivity strength of children with ASD was significantly higher during visual stimulation than during the quiet test. Comparison between the ROI–ROI functional connectivity strengths revealed significant differences in the connectivity strength of the RDLPFC/LOL, LDLPFC/LIPL, mPFC/RPMC, mPFC/LPMC, mPFC/LIPL, ROL/RPM, ROL. RIPL, ROL/LIPL, and LOL/LIPL. Extremely significant differences were observed between the ROL/RPMC and ROL/RIPL.ConclusionAnimated video modeling can improve visual perception and information processing in children with ASD, by strengthening the functional connectivity between the occipital and inferior parietal cortices.